Super edge-magic labeling of accordion and bracelet graphs - Baig A.Q.,; Afzal, Hafiz U.,; Imran M.,; Bashir M.S.,; Qureshi R.J., (Utilitas Mathematica, 2017)
Let G = (V, E) be a finite, simple and undirected graph with vertex set V(G) and edge set E(G). Graph G is called edge-magic if there exists a bijective function f, f: V(G) ∪ E(G) {1,2,..., |V(G)| + |E(G)|} such that f(u) + f(uv) + f(v) is a constant for each edge uv ϵ E(G). An edge-magic labeling f is called super edge-magic if the vertices are labeled with the smallest possible numbers. In this paper, we are dealing with the super edge-magic labeling of accordion and bracelet graphs.